Optimal Stable Approximation for the Cauchy Problem for Laplace Equation - Hongfang Li; Feng Zhou (Advances in Mathematical Physics)
Cauchy problem for Laplace equation in a strip is considered. The optimal error bounds between the exact solution and its regularized approximation are given, which depend on the noise level either in a Hölder continuous way or in a logarithmic continuous way. We also provide two special regularization methods, that is, the generalized Tikhonov regularization and the generalized singular value decomposition, which realize the optimal error bounds.